Evaluasi Implementasi Sistem Zonasi Pendidikan (Studi Kasus di SMP Negeri 2 dan 7 Purwokerto) - Irna Sulistiani; Alizar Isna; Sendy Noviko (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2020)
Since the 2017/2018 school year the Banyumas Regency government has been organizing Acceptance of New Students at the junior high school level, one of which uses the zoning system. This is motivated because the quality of education in Banyumas Regency especially at the JHS level is uneven, as evidenced by the naming of favorite and non-favorite schools in the community. Since the implementation of the zoning system in Banyumas Regency has created new problems. This study aims to evaluate the implementation of education zoning policies in JHS 2 and 7 Purwokerto based on the applicable policy guidelines and to determine the supporting and inhibiting factors of JHS 2 and 7 Purwokerto in achieving the objectives of the education zoning system policy. The method used in this research is qualitative. The selection of informants uses purposive sampling technique. Data collection uses in-depth interviews, observation and documentation study. Data analysis method used is an interactive analysis method. The results showed that JHS 2 Purwokerto as a favorite school and JHS as a non-favorite school had complied with the applicable policy guidelines, there were supporting factors which were the decentralization of power from the central government to regional governments and there were inhibiting factors namely the presence of blank spots and the desire of the community to enter favorite schools. The findings of the study are that JHS 7 Purwokerto as a non-favorite school has not been able to capture children of good quality because it is inferior to the 15% quota for achievement paths so that children who have good grades prefer to enroll in schools that are considered favorites. The school should also do active socialization and publication related to the achievements obtained to prospective students and parents of students, it is hoped that in this way it can generate trust to attend school at the school.